AVE 0991 Suppresses Astrocyte-Mediated Neuroinflammation of Alzheimer’s Disease by Enhancing Autophagy - Deng Y; Wang SY; Wang QG; Xu ZH; Peng Q; Chen SY; Zhu L; Zhang YD; Duan R (Dove Medical Press, 2023)
Yang Deng,1,* Si-Yu Wang,2,* Qing-Guang Wang,3,* Zhao-Han Xu,2 Qiang Peng,2 Shuai-Yu Chen,2 Lin Zhu,2 Ying-Dong Zhang,1,2 Rui Duan1,2 1Department of Neurology, Nanjing First Hospital, China Pharmaceutical University, Nanjing, People's Republic of China; 2Department of Neurology, Nanjing First Hospital, Nanjing Medical University, Nanjing, People's Republic of China; 3Department of Neurology, Jiangyin Hospital Affiliated to Nantong University, Jiangyin, People's Republic of China*These authors contributed equally to this workCorrespondence: Ying-Dong Zhang; Rui Duan, Department of Neurology, Nanjing First Hospital, China Pharmaceutical University, No.68, Changle Road, Nanjing, Jiangsu, People's Republic of China, Email zhangyingdong@njmu.edu.cn; duanruicpu@163.comPurpose: Our previous study has shown that AVE 0991, a nonpeptide analogue of Ang-(1-7), ameliorates cognitive decline and inhibits NLRP3 inflammasome of astrocytes in Alzheimer's disease model mice. Additionally, several studies have suggested that activation of autophagy appears to effectively inhibit the progression of neuroinflammation. However, it is unclear whether AVE 0991 can modulate astrocyte autophagy to suppress neuroinflammation in Alzheimer's disease.Materials and Methods: APP/PS1 mice and Aβ-treated primary astrocytes were used as the research objects in vivo and in vitro, respectively. Water maze test was used to evaluate cognitive function of mice, Nissl staining and immunofluorescence staining was used to assess neuronal damage. ELISA kits were used to detect the levels of Ang-(1-7) and Aβ in the cortex, and qRT-PCR was used to detect the expression of cortical inflammation-related mediators. The expression of autophagy-related proteins in cortex were detected by Western blot. The upstream molecular responses involved in inflammation inhibition by AVE 0991 were validated by means of using the Mas1 antagonist and autophagy inhibitor.Results: We found that 30 days of intraperitoneal administration of AVE 0991 improved. Aβ deposition, neuronal death, and cognitive deficits in APP/PS1 Alzheimer's disease model mice. Moreover, AVE 0991 treatment greatly suppressed astrocyte-mediated inflammation and up-regulated the expression of autophagy. Furthermore, the inhibitory effect of AVE 0991 on the expression of inflammatory factors was reversed by 3-MA, an autophagy inhibitor.Conclusion: These findings suggest that regulation of autophagy is critical for inhibiting astrocyte neuroinflammatory responses and demonstrate a potential neuroprotective mechanism by which AVE 0991 could suppress neuroinflammatory responses by enhancing autophagy.Keywords: AVE 0991, neuroinflammation, Alzheimer, autophagy, astrocytes